Morphoscopic changes in Iraqi territorial waters and their border repercussions - Al-Mahmood, Hassan K. H. (Iraqi Journal of Aquaculture, 2023)
Abstract The present study includes the analysis of the morphological change in the Iraqi coastline in Khor Abdullah and the entrance to the Shatt Al-Arab (Al-Ruka Channel), as the northwestern region of the Arabian Gulf is exposed to different erosion and depositions due to the suspended sedimentary load, The comparison between the periods studied showed severe erosion in some coastal areas and depositions in other parts, which led to changes in the shape and extension of the barriers or the sedimentary tongues and made them prominent, especially in the shallow sites (shoals) areas at the entrance to Khor Abdullah and Khor Shaitanah, and those changed parts appear in the maps of the British Admiralty, which draw detailed curves surrounding the varying depths. The extension of the suspended sedimentary load at the head of the Arabian Gulf amounted to 11,014 km2 in the year 2003, which expanded in 2011 to 12,680 km2, by adding suspended sediments of about 1,676 km2 to 6,452,600 tons over 8 years, at a rate of 806.575 tons annually, or 8.5% of the volume of suspended sediments in 1996 due to the decrease of the river flows from the Tigris, Euphrates, and Karun. The line of the lowest tide (zero line) showed a change in the cross-section of the Iraqi waterway lines that it shares with Iran and Kuwait, affecting the location of the approved border line between Iraq and Kuwait, and the largest change was in the width of the entrance to the Shatt Al-Arab (Al-Ruka Channel), and this was influenced by the erosion, sedimentation patterns, and deflection of tidal currents, as well as the temporary effect of port activities in Khor Abdullah. The extension of Abdullah’s Marqat at Ras Al-Bishah reached 15.5 km in 2003, its extension became 17.2 km in 2019 with a varying range of 1.7 km in 16 years, which has increased at lower rates in recent years due to the decrease in the sedimentary load of rivers to legalize water releases. The maximum change in Khor Abdullah in the middle part was 453 meters, which is a contraction in favor of Kuwait at a rate of 453 meters, and in the middle of the Al-Ruka Channel with an average width of 403 meters in favor of Iran, expansion in favor of Iraq was at a rate of 152 and 42 meters at the entrance and middle of Khor Shaitana.